"Pour le bien des enfants?" ("For the Good of the Children?"): Critical News Media Analysis of Deficit Discourses in the Expansion of Quebec's Kindergarten Program in 1960-1962 and 2018 - Valade, Tifanie (Université d'Ottawa / University of Ottawa, 2025)
This research project explored historic and current interventionist and deficit-based discourses in news media related to the universalization of kindergarten education in Quebec. Public debates surrounding the universalization of kindergarten for 5-year-olds in the early 1960s, during the Quiet Revolution, a period of rapid modernization and change, were compared to public debates during the 2018 provincial election where the universalization of kindergarten for 4-year-olds was proposed. A series of 196 news articles were analyzed via a critical, intersectional feminist poststructuralist lens, using critical thematic analysis. Themes developed from news media data from the 1960s included topics related to psychological intervention and the normalizing function of kindergarten, views of potentially deficient mothers and their replacement by kindergarten teachers, as well as fears of juvenile delinquency tied to understandings of modernity. From the election period in 2018, themes related to early schooling as a panacea for vulnerability were discussed, as well as shifting discourses tied to motherhood/parenting, the spectre of the "bad mother", and anxieties surrounding Québécois identity and nationhood. Finally, deficit discourses tied to neoliberal influences and human capital theory in early years education were addressed. Similarities and differences between the two time periods were noted, as well as shifts in the inclusion or exclusion of specific voices in public discourse.
Keywords: kindergarten; early childhood education; Quebec history; l'histoire du Québec; news media; children; newspaper analysis; public policy